Human Capital, Consumption, and Housing Wealth in Transition - Jarko Fidrmuc; Matus Senaj (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2012)
This paper focuses on human capital and physical capital of households in Slovakia during the economic reforms of the last two decades. We compare households who entered the labor market before and after the economic reforms in 1990. On the one hand, we study the returns to education by different labor market cohorts using household consumption surveys. On the other hand, we analyze the determinants of housing wealth and its impact on consumption. We show that old cohorts are characterized by lower returns to human capital and consumption levels, but higher housing wealth. Thus, we do not identify a clear pattern of winners and losers from transition.
Keywords: D12; J24; C31; 330